Developing Independent Learners through Metacognitive Self-Assessment Strategies in Anthropology Education Based on Outcome-Based Education - Dimas Ario Sumilih; Atma Ras (Universitas Negeri Makassar, 2026)
This article discusses the development of independent learners through metacognitive self-assessment strategies in anthropology education based on Outcome-Based Education at the Department of Anthropology, Faculty of Social Sciences and Law, Makassar State University. This study is motivated by the need for anthropology education that not only emphasises mastery of concepts regarding humans, culture, society, identity, and social change, but also requires students to be able to consciously plan, monitor, assess, and improve their learning processes. The method used is a conceptual study employing a contextual literature review approach, examining literature on metacognition, self-evaluation, independent learning, formative assessment, anthropology education, and the principles of Outcome-Based Education. The results of the study indicate that metacognitive self-evaluation can be integrated through reflective rubrics, learning journals, self-assessment, guiding questions, and formative feedback to strengthen the relationship between learning outcomes, classroom activities, assessment, and evidence of student competence. This strategy contributes to shaping anthropology students who are reflective, critical, responsible, and capable of applying anthropological knowledge analytically to understand socio-cultural realities.